6‐Gingerol, an active constituent of ginger, attenuates lipopolysaccharide‐induced oxidation, inflammation, cognitive deficits, neuroplasticity, and amyloidogenesis in rat. Issue 4 (24th February 2021) - Adetuyi, Babatunde Oluwafemi; Farombi, Ebenezer Olatunde
Abstract: This study examined the protective effect of 6‐Gingerol (6G) against lipopolysaccharide (LPS)‐induced cognitive impairments, oxidative stress, neuroplasticity, amyloidogenesis, and inflammation. Male rats were allocated into six groups in this manner; Group I placed on normal saline only. Group II was treated for 7 days with LPS alone intraperitoneally at 250 µg/kg body weight (bw). Group III received 6G alone at 50 mg/kg bw orally for 14 days. Groups IV and V received 6G at 20 and 50 mg/kg bw for 7 days, respectively, and LPS for another 7 days to induce neurotoxicity. Group VI received 5 mg/kg bw of donepezil for 7 days and LPS for 7 days. Pretreatment with 20 and 50 mg/kg bw of 6G protected against LPS‐mediated learning and memory function, and also locomotor and motor deficits. Besides, 20 and 50 mg/kg bw 6G mitigated LPS‐induced alteration in markers of oxidative stress. Furthermore, induction of amyloidogenesis associated with disruption of histoarchitecture and high expression of interleukin 1β, inducible nitric oxide synthase, amyloid precursor protein (APP), β‐secretase 1, and brain‐derived neurotrophic factor by LPS was mitigated by the two doses of 6G in the rat hippocampus and cerebral cortex region of the brain. 6G pretreatment at the two doses mitigated LPS‐mediated histopathological changes in the hippocampus and cerebral cortex of rats. Overall, our results demonstrate that the protective effect of 6G is mediated through the reversal of neurobehavioral deficit, oxidative stress, inflammation, and amyloidogenesis, thus making 6G a possible chemoprophylactic agent against brain injury as a result of LPS exposure. Practical applications: In the search for a holistic prevention of inflammation‐associated neurodegeneration, nutraceuticals are becoming prominent. Hence, this study presents 6G, an active constituent of ginger, as a chemoprotective, antioxidant, and anti‐inflammatory agent, which is able to ameliorate cognitive impairments, oxidative stress, neuroplasticity, amyloidogenesis, and inflammation in LPS‐induced rat model of neuroinflammation. Abstract : 6G protected against LPS‐mediated learning function, memory function, locomotor and motor deficits, mitigated LPS‐induced alteration in markers of oxidative stress, inhibited the induction of amyloidogenesis associated with disruption of histoachitecture and high expression of interleukin 1β, inducible nitric oxide synthase, amyloid precursor protein, β‐secretase 1, and brain‐derived neurotrophic factor by LPS in the hippocampus and cerebral cortex of rat brain. 6G pretreatment also mitigated LPS‐mediated histopathological changes in the cerebral cortex and hippocampus of rats.